2014
DOI: 10.1115/1.4026317
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Uncertainties During Assessment of Serial Coronary Stenoses: An In Vitro Study

Abstract: Currently, the diagnosis of coronary stenosis is primarily based on the well-established functional diagnostic parameter, fractional flow reserve (FFR: ratio of pressures distal and proximal to a stenosis). The threshold of FFR has a "gray" zone of 0.75-0.80, below which further clinical intervention is recommended. An alternate diagnostic parameter, pressure drop coefficient (CDP: ratio of trans-stenotic pressure drop to the proximal dynamic pressure), developed based on fundamental fluid dynamics principles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…The CDP value is not limited within a small range; an accurate cut-off value can be obtained for the CDP after human clinical trials. The CDP is considered a viable diagnostic parameter used in clinical settings [ 24 , 41 ]. However, it is clinically hard to obtain the proximal velocity during the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The CDP value is not limited within a small range; an accurate cut-off value can be obtained for the CDP after human clinical trials. The CDP is considered a viable diagnostic parameter used in clinical settings [ 24 , 41 ]. However, it is clinically hard to obtain the proximal velocity during the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Several theoretical, experimental, animal and clinical studies have demonstrated the usefulness of measuring FFR to assess the hemodynamic significance of two serial stenoses (Pijls et al 2000;D'Souza et al 2014). However, the effects of the distance separating the two lesions (Dss) and the combined severity of the two serial stenoses (S1, S2) on the global and intermediate FFR amplitudes remain unclear.…”
Section: Introductionmentioning
confidence: 99%